Analysis of the Level of Satisfaction and Importance among Trainees towards Distance Training in the Covid-19 Pandemic Era - Azwar Iskandar; Ita Hartati (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
This study aims to analyze the level of satisfaction and importance among trainees towards distance training and identify the strengths and weaknesses of distance training implementation so that the organizers can maximize the satisfaction of the trainees towards the implementation of distance training. This research used quantitative and qualitative analysis within the framework of Level 1 (Reaction) of the Kirkpatrik Evaluation Model, as well as the Importance Performance Analysis (IPA) method. The results showed that: (1) the trainees were very satisfied with the implementation of distance training; (2) the implementation of distance training is considered very important to be implemented; (3) Some evaluation indicators have positive gap values, while others have negative gap values, meaning that some evaluation indicators have not met the expectations of stakeholders; and (4) most evaluation indicators are in quadrants A and B, meaning that they either must be prioritized to improve the performance, or maintained because they are already considered good. Therefore, the Financial Education and Training Agency through work units in the region, especially the Makassar branch, needs to improve the performance of distance training implementation, especially in the evaluation items/indicators in quadrant A to increase the satisfaction of participants in the next training sessions.